Basic Concept and Approach to the Psychodermatology Patient - Hasbiallah Yusuf (HM Publisher, 2022)
The association of the nervous system with skin is well documented, with close anatomical, physiological and functional connections between skin and nervous system, known to be ontogenetically related. Psychodermatology is a branch of science that is still underdeveloped, described concerning possible interaction between dermatology and psychiatry. The physician often feels challenges for treating patients with Psychodermatology conditions, due to the difficulty of extracting the medical history, which makes a lot of misunderstanding between clinical symptoms and the diagnostic criteria. The treatment of psychodermatological disorders focuses on elaborating on how an effective approach to the psychodermatology patient can help build such an alliance and improve outcomes. The aim of the approach is to improve function, reducing physical distress, diagnosing ​and treating depression and anxiety associated with skin ​disease, managing social isolation, and improving self-esteem of the patient.